AB1329 Current and previous use of biologics in rheumatoid arthritis patients. Data from the norwegian biorheuma project. (23rd January 2014) - Haugeberg, G.; Bader, L.; Rødevand, E.; Haaland, K.; Gjesdal, C.; Storesund, B.; Gulseth, H.C.; Haavardsholm, E.; Mikkelsen, K.
Abstract : Background: Norway (4.9 million inhabitants) is among the countries with the highest proportion of patients with inflammatory joint disorders treated with biologic drugs (1). The total cost for biologic treatment in Norway has been estimated to be ∼800 million Nkr (∼105 million Euro) for rheumatoid arthritis (RA). In 1999 the first biologic drug, the TNF inhibitor Infliximab, became available for clinical use in Norway. In the following years other TNF inhibitors has become available (etanercept (2000), adalimumab (2004), certolizumab pegol (2010) and golilumumab (2010)) and other biologic treatments which includes IL-6 inhibition (tocilizumab 2009), T-cell inhibition (abatacept 2007) and B-cell depletion (rituximab 2006). Objectives: To explore which biologic drugs RA patients were currently using, or had been using, assessed by the end of 2011 in Norway. Methods: In 2009 the BIORHEUMA project (BIOlogic treatment of patients suffering from inflammatory RHEUMAtic disorders in Norway) was established. The aim was 1. To implement the use of outcome measures and the T2T recommendations in daily clinical practice by the use of a designated computerized system. 2. To obtain unselected real life data on clinical status and treatment practices in patient with inflammatory rheumatic joint disorders. All participating centers had to use the GoTreatIT Rheuma computer software system (www.diagraphit.com ) to monitor their patients on biologic treatment. By the end of 2011 nine out of the ten participating centers reported to have implemented the clinical standard of monitoring RA patients on biologics. Results: In 2011 a total of 7206 RA patients had been assessed at the participating centers and registered in the computer system. Among them 2745 (38.1%) RA patients were registered as current users and a total of 3286 (45.5%) as ever users of biologic drugs. The distribution of current and previous use of the biologic drugs among ever users of biologics is shown in the table . Ever use of 1 biologic drug was seen in 56.9%, 2 biologics in 23.5%, 3 biologics in 11.3% and 4 or more biologics in 8.3%. Conclusions: As expected TNF inhibitors are the most frequent used biologic drugs for treatment of RA patients in Norway, with etanercept being the most frequently used. Among the other modes of action Rituximab is the most frequently used biologic drug. References: Jonsson Bet al. Eur J Health Econ. 2008 Jan;8 Suppl 2:S61-86. Disclosure of Interest: G. Haugeberg Shareholder of: DiaGraphIT, Grant/Research support from: Supported by Roche, Pfizer, Abbott, L. Bader: None Declared, E. Rødevand: None Declared, K. Haaland: None Declared, C. Gjesdal: None Declared, B. Storesund: None Declared, H. C. Gulseth: None Declared, E. Haavardsholm: None Declared, K. Mikkelsen: None Declared